Identifying macroeconomic shocks using firm-level data: Material shortages in the German manufacturing sector - Friederike Fourné; Lara Zarges (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2025)
We leverage micro-data to identify macro shocks in time series settings. We exploit firm-level forecast errors on prices and production along with information on production impediments to construct a shock series capturing input material constraints. Our approach allows to separately identify periods of tightening and easing material supply shocks. We find that both types of shocks have different implications for economic activity: tightening shocks instantaneously push prices up whereas an easing of material constraints instantaneously boosts production and triggers a more sluggish response of prices. Decomposing the instrument into its individual components allows to contrast the response to input material shocks to any other generic supply shock. We also show that the construction of the instrument is robust to variations in the underlying identification assumptions at the micro-level.
Keywords: C32; C36; E31; E32; 330; material shortages; survey data; firm expectations; inflation; external instruments